Factors related to the level of readiness in accrual-based accounting implementation among Malaysian public health care in Northern Region - Nur Shawalliza Yusof (2019)
The aim of this study was to identify the level of readiness in the implementation of accrual-based accounting among Malaysian public healthcare in the Northern region. It also examined therelationship between human resources competency, software and technology capability,accounting policies and standards suitability and the level of readiness in the implementation ofaccrual-based accounting. Quantitative approaches were used in this study with questionnaire as theresearch instrument. Data were collected from a sample of 200 administrative officers in theFinance Department at 20 public hospitals and state health departments. Descriptive andinferential analysis techniques were used to analyse the data. The finding showed that the level ofreadiness to implement accrual-based accounting in Malaysian public healthcare wasmoderately high (M = 3.97, SD = 0.719). The results also revealed that there were significantrelationships between human resources competency (r=0.300, p=0.001), software andtechnology capability (r=0.514, p=0.001) and accounting policies and standards suitability(r=0.706, p=0.001) and the level of readiness to implement accrual-based accounting. Theresults implicated that users of accounting system in Northern Malaysian public healthcare areready to implement accrual-based accounting. However, improvement should be directedtowards relevant areas as identified in the study to ensure a more successful andbeneficialimplementation of this new accounting system in Malaysian public sector.